VALIDATION OF TRICHOSANTHES KINABALUENSIS RUGAYAH (CUCURBITACEAE) - RUGAYAH RUGAYAH (Research Center for Biology, 2000)
In the revision of the cucurbitaceous genus Trichosanthes in Malesia by Rugayah & W.J.J.O. de Wilde (Reinwardtia 11(4): 262. 1999), the type of the proposed new species T. kinabaluensis Rugayah was erroneously indicated as consisting of two collections, viz. Chew, Corner & Stainton 2830 and De Wilde & Duyfjes SAN 139472. This latter appeared to be contrary to art. 37.3 of the International Code of Botanical Nomenclature (Tokyo Code, 1994), rendering the new species invalid. This species is validated below by indicating a single type. I am grateful to Dr. Dan H. Nicolson (US Washington), who kindly made me aware of the mistake.